2013
DOI: 10.1007/s12310-013-9115-3
|View full text |Cite
|
Sign up to set email alerts
|

Implementation Science in School Mental Health: Key Constructs in a Developing Research Agenda

Abstract: In this paper, we propose an implementation science research agenda as it applies to school mental health (SMH). First, we provide an overview of important contextual issues to be considered when addressing research questions pertinent to the implementation of mental health interventions in schools. Next, we critically review three core implementation components: (a) professional development and coaching for school professionals regarding evidence-based practices (EBPs); (b) the integrity of EBPs implemented i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
142
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 185 publications
(155 citation statements)
references
References 74 publications
6
142
0
1
Order By: Relevance
“…During calls, clinicians and expert consultants (a) troubleshot use of the SB-MHITS technology and (b) supported clinicians in incorporating MBC practices into their routine services. Given uncertainty in the field about the dosage of consultation required to adequately support clinicians following training (Nadeem et al, 2013; Owens et al, 2014), the emphasis of the current project on maximizing consultation efficiency, evaluated the immediate (i.e., one week) effects of consultation calls on clinician behavior. Results indicated that the effects of consultation calls on MBC practices in the subsequent week were either significant or approached significance for assessment feedback and administration, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…During calls, clinicians and expert consultants (a) troubleshot use of the SB-MHITS technology and (b) supported clinicians in incorporating MBC practices into their routine services. Given uncertainty in the field about the dosage of consultation required to adequately support clinicians following training (Nadeem et al, 2013; Owens et al, 2014), the emphasis of the current project on maximizing consultation efficiency, evaluated the immediate (i.e., one week) effects of consultation calls on clinician behavior. Results indicated that the effects of consultation calls on MBC practices in the subsequent week were either significant or approached significance for assessment feedback and administration, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the follow-up periods were relatively short in the three studies that examined sustainment. Despite the limited time frame of conducting research in school settings (Owens et al, 2014), it may be of critical importance to explore long-term sustainment of intervention effects into the next school year and beyond.…”
Section: Discussionmentioning
confidence: 99%
“…Because much of our collaborative effort focuses on appropriate use of research evidence, the SMART Center endorses and actively pursues the implementation science research agenda recently articulated by Owens and colleagues (2014) surrounding professional development and coaching. For example, how much coaching is necessary following training to produce sustained practitioner behavior change?…”
Section: Discussionmentioning
confidence: 99%